Murine Virus-Induced Proteins Synthesized by Hamster Tumor Cells Transformed by, But Not Producing, Murine Sarcoma Virus - Ikegami, Nobuko (1974)
The 8303 hamster tumor cells transformed by Moloney strain of murine sarcoma virus (M-MSV), but which do not produce virus, do contain murine virus-induced proteins. The virus-induced proteins within the cell were identified either as free proteins or in association with membranous material, including the plasma membrane. In addition, some were excreted by the 8303 hamster tumor cells into the growth medium. Most virus-induced proteins were larger than 68,000 daltons, and they did not dissociate into components of smaller size in the presence of detergent and a reducing agent. A small amount of virus-induced protein with a molecular weight of less than 20,000 was also found in the hamster tumor cells. No virus-specific proteins with the identical antigenic specificity or size of the major internal group specific antigen (molecular weight about 30,000) of the murine leukemia viruses were present in these cells. There is a common cell surface antigen present in three other tumor cell lines, both virus-producing and non-virus-producing, identical in reactivity to that of the murine virus-induced antigen of the 8303 hamster tumor cell. This antigen is not present on the cell surface of normal mouse embryo cells.